Arylesterase Activity of HDL Associated Paraoxonase as a Potential Prognostic Marker in Patients With Sepsis and Septic Shock—A Prospective Pilot Study - Reisinger, Alexander C.; Schuller, Max; Holzer, Michael; Stadler, Julia T.; Hackl, Gerald; Posch, Florian; Marsche, Gunther; Sourij, Harald; Ekart, Robert; Eller, Kathrin; Eller, Philipp (Frontiers in Medicine, 2020)
Background: High-density lipoprotein (HDL) plays an essential role in the immune system and shows effective antioxidative properties. We investigated correlations of lipid parameters with the SOFA score and the prognostic association with mortality in sepsis patients admitted to ICU. Methods: We prospectively recruited consecutive adult patients with sepsis and septic shock, according to sepsis-3 criteria as well as non-sepsis ICU controls. Results: 53 patients with sepsis (49% with septic shock) and 25 ICU-controls without sepsis were enrolled. Dyslipidemia (HDL-C<40mg/dL) was more common in sepsis compared to non-sepsis patients (85% vs 52%, p=0.002). Septic patients compared to controls had reduced HDL-C (14 vs. 39mg/dL, p<0.0001), lower arylesterase activity of the antioxidative paraoxonase of HDL (AEA) (67 vs 111mM/min/mL serum, p<0.0001), and a non-significant trend towards reduced cholesterol efflux capacity (9 vs 10%, p=0.091). We observed a strong association between higher AEA and lower risk of 28-day (per 10mM/min/mL serum increase in AEA: Odds Ratio (OR)=0.76, 95%CI: 0.61-0.94, p=0.01) and ICU mortality (per 10mM/min/mL serum increase in AEA: OR=0.71, 95%CI: 0.56-0.90, p=0.004) in the sepsis cohort in univariable logistic regression analysis. AEA was confirmed as an independent predictor of 28-day and ICU mortality in multivariable analyses. AEA discriminated well regarding 28-day/ICU mortality in AUROC analyses. In survival analysis, 28-day mortality estimates were 40% and 69% with AEA ≥ / < the 25th percentile of AEA’s distribution, respectively (log-rank p=0.0035). Conclusions: Both compositional and functional HDL parameters are profoundly altered during sepsis. In particular, the functionality parameter AEA shows promising prognostic potential in sepsis patients.